Cisplatin and a potent platinum(IV) complex-mediated enhancement of TRAIL-induced cancer cells killing is associated with modulation of upstream events in the extrinsic apoptotic pathway - Vondálová Blanárová, Olga; Jelínková, Iva; Szöor, Arpád; Skender, Belma; Soucek, Karel; Horváth, Viktor; Vaculová, Alena; Andera, Ladislav; Sova, Petr; Szöllosi, János; Hofmanová, Jirina; Vereb, György; et al. (Carcinogenesis, 2011)
TRAIL (tumor necrosis factor-related apoptosis-inducing ligand) can selectively trigger apoptosis in various cancer cell types. However, many cancer cells are resistant to death receptor-mediated apoptosis. Combination therapy with platinum complexes may affect TRAIL-induced signaling via modulation of various steps in apoptotic pathways. Here, we show that cisplatin or a more potent platinum(IV) complex LA-12 used in 20-fold lower concentration enhanced killing effects of TRAIL in human colon and prostate cancer cell lines via stimulation of caspase activity and overall apoptosis. Both platinum complexes increased DR5 surface expression in colon cancer cells. Small interfering RNA-mediated DR5 silencing rescued cells from sensitizing effects of platinum drugs on TRAIL-induced caspase-8 activation and apoptosis, showing the functional importance of DR5 in the effects observed. In addition, both cisplatin and LA-12 triggered the relocalization of DR4 and DR5 receptors to lipid rafts and accelerated internalization of TRAIL, which may also affect TRAIL signaling. Collectively, modulations of the initial steps of the extrinsic apoptotic pathway at the level of DR5 and plasma membrane are important for sensitization of colon and prostate cancer cells to TRAIL-induced apoptosis mediated by LA-12 and cisplatin.
Keywords: nádorové buněčné linie; signální transdukce; apoptóza; průtoková cytometrie; transport proteinů; RNA interference; separace buněk; Cisplatin; Microscopy, Confocal; cisplatina; Signal Transduction; amantadin; Organoplatinum Compounds; RNA Interference; Cell Line, Tumor; Amantadine; konfokální mikroskopie; Cell Separation; TRAIL receptory; western blotting; polymerázová řetězová reakce s reverzní transkripcí; Flow Cytometry; Neoplasms; TNF-Related Apoptosis-Inducing Ligand; Blotting, Western; Humans; fluorescenční protilátková technika; organoplatinové sloučeniny; nádory; Protein Transport; Receptors, TNF-Related Apoptosis-Inducing Ligand; Fluorescent Antibody Technique; Reverse Transcriptase Polymerase Chain Reaction; Apoptosis; lidé; protein TRAIL